Decolonial Processes in Modern Ukrainian Literature through the Disclosure of the Soviet Man Image. City Space as One of the Identity-Forming Factors - Pidburtna, D. (Місто: історія, культура, суспільство, 2023)
A post-colonial approach to literary studies of modern literature, in particular Ukrainian, has gained considerable popularity over the last decade. Clearly, the collapse of the Soviet Union and the subsequent attainment of independence have laid the foundation for the development of post-colonial studies in our territory. Injuries inflicted during the long period of colonisation (although not all researchers agree to use this term, noting the absence of a key characteristic of the colony — “a large body of water” is missing) have been understood and reflected both in literature and its researchers. However, currently we are at a stage, when writers are moving beyond the reflection typical for post-colonial viewpoints, delving into the exploration of logical connections between events and their consequences, examining ways to process these traumas. Therefore, in modern research, the decolonial approach, which emerges as a branch of postcolonial thought, is more relevant. In particular, this is discussed by Agnieszka Matusiak and Tamara Hundorova. Tamara Hundorova identifies a unique form of decolonial aesthetics in Ukrainian literature — aesthesis. This is the manifestation of the unknown, even the opposite of the generally accepted modern concept of “aesthetics” — corporeality, sensuality, and mystical practices . Agnieszka Matusiak observes that modern Ukrainian science and culture have undergone a ‘decolonial turn’ (decolonial-detotalitarian, as she calls this phenomenon, a complete shift in emphasis in discussions about Donbas). Decolonization is intrinsically linked in Ukrainian realities with de-Sovietization. While at the governmental level, this occurs through changing street names and re-evaluating Soviet political figures, people raised under this system find it challenging to shed an identity formed under vastly different values and conditions. The article aims at o showcase the depiction and transformation of the Soviet man in modern Ukrainian literature, illustrating changes that signify a shift towards a decolonial perspective. Also of interest are the aspects of traumatic memory and the identity crisis of characters, invariably linked with the disintegration of the Soviet Union. Постколоніальний підхід до літературознавчих досліджень сучасної літератури, зокрема української, доволі популярний останні десятиліття. Очевидно, ґрунтом для розвитку постколоніальних студій на наших теренах став розвал Радянського Союзу та здобуття незалежності. Травми, завдані довгим періодом колонізації (хоча не всі дослідники воліють вживати це слово, адже відсутня одна із головних ознак колонії — «велика вода»), осмислювала й рефлексувала і література, і її дослідники. Та наразі ми знаходимося на тому етапі, коли письменники відходять від рефлексій, притаманних постколоніальному погляду, і переходять до пошуку логічних ланцюжків між подіями та їхніми наслідками, шляхів проживання травм. Тож у сучасних дослідженнях більш актуальний деколоніальний напрям, який є одним із відгалужень постколоніальних вчень. Зокрема, про це говорять Аґнєшка Матусяк та Тамара Гундорова. Тамара Гундорова знаходить у сучасній українській літературі особливу форму деколоніальної естетики — естезис. Це оприявлення невидимого, навіть протилежного загальноприйнятому модерному поняттю «естетика» — тілесності, чуттєвості, містичних практик. Аґнєшка Матусяк визначає, що в сучасній українській науці та культурі відбувся деколоніальний поворот (деколоніально-детоталітарний, як вона називає це явище відносно зміщення акцентів у дискусіях навколо Донбасу). Деколонізація дійсно дуже міцно пов’язана в українських реаліях із дерадянізацією. І якщо на рівні влади вона відбувається шляхом зміни назв вулиць та переосмислення постатей радянських політичних діячів, то людям, які були виховані в цій системі, важко відмовлятися від ідентичності, яка базувалась на кардинально інших цінностях та формувалась в інакших умовах. Стаття покликана через репрезентацію образу радянської людини, його функціонування та трансформації в сучасній українській літературі показати зміни, які свідчать про зміну оптики на деколонізаційну. Цікавими є також аспекти травматичної пам’яті та кризи ідентичності персонажів, яка так чи інакше пов’язана з розпадом Радянського Союзу.